Analisis perbandingan rencana strategi pada bank swasta konvensional - Salsabila, Gardena; Cahyati, Dwi Nur; Rachmadaniyah, Shafa Ardhia (Maliki Interdisciplinary Journal, 2024)
Banking is a business that collects public funds in the form of savings and distributes them to the community or customers to improve the standard of living of many people. This is based on Law Number 10 of 1998 which defines banking as a business that collects money from the public through loans or other means to improve the welfare of many people. In the journal written by the author, he explains the strategic plans of three banks, namely Bank Bca, Bank Danamon and Bank Maybank as well as a comparison of their strategic plans, where of course these three banks have several aspects which are then compared between one bank and another. The following are various aspects for comparison, namely management, marketing, finance, production, MIS and business processes which will later be compared one by one aspects of the three banks.